2021
DOI: 10.3390/biom11070924
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Transcription Machinery and Its Crosstalk with Nucleoid-Associated Proteins and Global Transcription Factors

Abstract: The coordination of bacterial genomic transcription involves an intricate network of interdependent genes encoding nucleoid-associated proteins (NAPs), DNA topoisomerases, RNA polymerase subunits and modulators of transcription machinery. The central element of this homeostatic regulatory system, integrating the information on cellular physiological state and producing a corresponding transcriptional response, is the multi-subunit RNA polymerase (RNAP) holoenzyme. In this review article, we argue that recent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 140 publications
(216 reference statements)
0
14
0
Order By: Relevance
“…When high-resolution single-cell data of chromosome structure and chromosome dynamics will become available, one can start exploring these questions beyond the circle approximation employed here, in order to study the interplay of chromosomal dynamics and TF-based gene regulation in further detail 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…When high-resolution single-cell data of chromosome structure and chromosome dynamics will become available, one can start exploring these questions beyond the circle approximation employed here, in order to study the interplay of chromosomal dynamics and TF-based gene regulation in further detail 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic constraints of DNA supercoils by NAPs are, by and large, responsible for rendering the chromosome structure and gene expression interdependent. Both the abundance and composition of NAPs vary continuously forming temporal concentration gradients during the growth cycle [ 34 , 35 , 36 ], whereas their expression is in turn, regulated by ppGpp and/or by DNA supercoiling [ 1 , 37 , 38 , 39 , 40 , 41 , 42 ]. DNA supercoiling modulates not only the gene expression but also the efficiency of DNA binding by NAPs [ 43 , 44 , 45 , 46 ], whereas ppGpp can modulate the NAP-binding effect by protein modification [ 47 ].…”
Section: Gradients Of Regulatorsmentioning
confidence: 99%
“…Intrinsically curved DNA sequences were shown to facilitate the pinning of plectonemic supercoils upstream of the promoter [ 81 ]. Furthermore, the variations in canonical promoter elements such as the G/C content of the discriminator sequence (the sequence between the −10 hexamer and the transcription start site) and the length of the spacer between the −10 and −35 hexamers, were shown to be determinative for the promoter supercoiling response [ 40 , 42 , 82 , 83 , 84 , 85 , 86 ]. For example, the “stringent” promoters (such as stable RNA promoters) that are, respectively, down- and up-regulated by ppGpp and negative supercoiling are characterized by G/C-rich discriminators, short (16 bp) spacers, and suboptimal −35 hexamers as well as anisotropically bendable upstream activating sequences (UAS) forming coherently bent DNA microloops associated with RNAP [ 55 , 87 , 88 ].…”
Section: Role Of Local Sequence Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic position of key gene groups is widely conserved along the ori-ter axis following the temporal pattern of gene expression (17, 18, 21, 22). Thus, coding sequences expressed in exponential phase are physically associated to the oriC region while factors transcribed in stress situations or in stationary phase cluster close to the ter region (17, 21, 2326). Consistently, it was recently shown that some genes need a specific genomic location to achieve their function (16).…”
Section: Introductionmentioning
confidence: 99%